Psychoeducational Characteristics of Children with Hypohidrotic Ectodermal Dysplasia - Rolanda A. Maxim; Samuel H. Zinner; Hisako Matsuo; Theresa M. Prosser; Mary Fete; Terry L. Leet; Timothy J. Fete (The Scientific World Journal)
Objective. Hypohidrotic ectodermal dysplasia (HED) is an X-linked hereditary disorder characterized by hypohidrosis, hypotrichosis, and anomalous dentition. Estimates of up to 50% of affected children having intellectual disability are controversial. Method. In a cross-sectional study, 45 youth with HED (77% males, mean age 9.75 years) and 59 matched unaffected controls (70% males, mean age 9.79 years) were administered the Kaufman Brief Intelligence Test and the Kaufman Test of Educational Achievement, and their parents completed standardized neurodevelopmental and behavioral measures, educational, and health-related information regarding their child, as well as standardized and nonstandardized data regarding socioeconomic information for their family. Results. There were no statistically significant differences between the two groups in intelligence quotient composite and educational achievement scores, suggesting absence of learning disability in either group. No gender differences within or between groups were found on any performance measures. Among affected youth, parental education level correlated positively with (1) cognitive vocabulary scores and cognitive composite scores; (2) educational achievement for mathematics, reading, and composite scores. Conclusion. Youth affected with HED and unaffected matched peers have similar profiles on standardized measures of cognition, educational achievement, and adaptive functioning although children with HED may be at increased risk for ADHD.